'A most complex marriage arrangement': recent advances on heterostyly and unresolved questions. Issue 3 (21st October 2019) - Barrett, Spencer C. H.
Summary: Heterostylous genetic polymorphisms provide paradigmatic systems for investigating adaptation and natural selection. Populations are usually comprised of two (distyly) or three (tristyly) mating types, maintained by negative frequency‐dependent selection resulting from disassortative mating. Theory predicts this mating system should result in equal style‐morph ratios (isoplethy) at equilibrium. Here, I review recent advances on heterostyly, focusing on examples challenging stereotypical depictions of the polymorphism and unresolved questions. Comparative analyses indicate multiple origins of heterostyly, often within lineages. Ecological studies demonstrate that structural components of heterostyly are adaptations improving the proficiency of animal‐mediated cross‐pollination and reducing pollen wastage. Both neutral and selective processes cause deviations from isoplethy in heterostylous populations, and, under some ecological and demographic conditions, cause breakdown of the polymorphism, resulting in either the evolution of autogamy and mixed mating, or transitions to alternative outcrossing systems, including dioecy. Earlier ideas on the genetic architecture of the S ‐locus supergene governing distyly have recently been overturned by discovery that the dominant S‐ haplotype is a hemizygous region absent from the s ‐haplotype. Ecological, phylogenetic and molecular genetic data have validated some features of theoretical models on the selection of the polymorphism. Although heterostyly is the best‐understood floral polymorphism in angiosperms, many unanswered questions remain.